2022
DOI: 10.3390/cancers14174075
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Metabolome of Breast Tissues from Non-Hispanic Black and Non-Hispanic White Women Reveals Correlations between Microbial Dysbiosis and Enhanced Lipid Metabolism Pathways in Triple-Negative Breast Tumors

Abstract: Triple-negative breast cancer (TNBC) is an aggressive form of breast cancer that is non-responsive to hormonal therapies and disproportionately impact women of African ancestry. We previously showed that TN breast tumors have a distinct microbial signature that differs from less aggressive breast tumor subtypes and normal breast tissues. However, it is unknown whether these differences in breast tumor microbiota may be driven by alterations in microbial metabolites, leading to potentially protective or pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Both tumor and normal tissue adjacent to tumor (NAT) samples emphasized a specific microbiota in both NHB and NHW women, whereas, when compared to a matching NAT area, the microbial diversity in NHB TNBC cancer tissue was much reduced [252]. Smith et al (2022) reported that TNBC has a specific microbiota that differs from the less aggressive BC subtypes, emphasizing a correlation between host metabolic process changes and breast microbial dysbiosis in NHB and NHW women's breast cancers [253]. Thus, potential race-specific microbial biomarkers of BC correlate to genes involved in tumor aggressiveness, angiogenesis, migration and metastasis, as well as oncogenic signaling pathways GLI and Notch in a specific manner [36].…”
Section: Microbiomics-and Metagenomics-related Disparities In Breast ...mentioning
confidence: 99%
“…Both tumor and normal tissue adjacent to tumor (NAT) samples emphasized a specific microbiota in both NHB and NHW women, whereas, when compared to a matching NAT area, the microbial diversity in NHB TNBC cancer tissue was much reduced [252]. Smith et al (2022) reported that TNBC has a specific microbiota that differs from the less aggressive BC subtypes, emphasizing a correlation between host metabolic process changes and breast microbial dysbiosis in NHB and NHW women's breast cancers [253]. Thus, potential race-specific microbial biomarkers of BC correlate to genes involved in tumor aggressiveness, angiogenesis, migration and metastasis, as well as oncogenic signaling pathways GLI and Notch in a specific manner [36].…”
Section: Microbiomics-and Metagenomics-related Disparities In Breast ...mentioning
confidence: 99%
“…NGS technologies allow for rapid and comprehensive sequencing of the genetic material of the gut microbiome, revealing previously unknown microbial diversity and functional pathways 117,118 . This has led to the identification of specific microbial taxa and functional pathways associated with breast cancer development, such as changes in the abundance of certain bacteria or alterations in the production of specific metabolites 119 . Similarly, genome sequencing and single‐cell sequencing enable researchers to identify specific genetic pathways and interactions between microbial species in the gut that may contribute to breast cancer development 120 .…”
Section: Technological Advances In Breast/gut Microbiome Research: a ...mentioning
confidence: 99%
“… 117 , 118 This has led to the identification of specific microbial taxa and functional pathways associated with breast cancer development, such as changes in the abundance of certain bacteria or alterations in the production of specific metabolites. 119 Similarly, genome sequencing and single‐cell sequencing enable researchers to identify specific genetic pathways and interactions between microbial species in the gut that may contribute to breast cancer development. 120 By identifying these pathways and interactions, researchers may develop targeted therapies that modulate the gut microbiome to prevent or treat breast cancer.…”
Section: Technological Advances In Breast/gut Microbiome Research: a ...mentioning
confidence: 99%
“…Studies have shown that the breast microbiome biomass decreases in breast cancer patients [77]. Additionally, distinct microbial communities have been observed in breast tissues of non-Hispanic Black and non-Hispanic White women, with differences in microbiome composition by race, breast cancer stage, or breast tumor subtype [24,78]. Dysbiosis of microbiota may contribute to obesity and obesity-related diseases through various mechanisms, including energy harvesting, direct effects on gene expression, and direct or indirect effects of chronic inflammation [79].…”
Section: Etiology Of Microbiome Dysbiosis In Breast Cancermentioning
confidence: 99%